Strong-field nonsequential double ionization of Ar and Ne - Chen, Zhangjin; Liang, Yaqiu; Madison, D. H.; Lin, C. D. (My University, 2011)
We investigate the nonsequential double ionization (NSDI) of Ar and Ne based on quantitative rescattering theory (QRS). According to QRS theory, each elementary NSDI process can be calculated by multiplying the returning electron wave packet with appropriate differential electron-ion scattering cross sections. We include (e, 2e) and electron-impact excitation cross sections of Ar+ to obtain the correlated electron momentum spectra for the NSDI of Ar by few-cycle pulses to check the dependence of NSDI on the carrier-envelope phase. The results are compared to the ion momentum spectra from the recent experiment of Johnson et al. [Phys. Rev. A 83, 013412 (2011)]. Calculations have also been performed for Ar at another intensity to illustrate the intensity dependence of NSDI and to compare with the earlier data of Feuerstein et al. [Phys. Rev. Lett. 87, 043003 (2001)] and for Ne to illustrate the target dependence. We also address the presence of resonant capture processes in electron-ion collisions in the NSDI spectra.